2002
DOI: 10.1002/ijc.10793
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of prostate cancer associated with AA genotype of cyclin D1 gene A870G polymorphism

Abstract: CCND1 mRNA is alternatively spliced to produce 2 transcripts, and the splicing pattern may be modulated by a frequent A870G single-nucleotide polymorphism within the conserved splice donor site of exon 4. Several studies have suggested a significant association between the CCND1 genotype and onset or progression of various cancers. 0.679). However, in patients with high-grade or metastatic PCa, a significantly increased risk associated with the AA genotype compared to controls was observed, while no significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 27 publications
4
47
1
1
Order By: Relevance
“…The A870 polymorphism of cyclin D1 is associated with increased PCa risk (26,27). However, the prevalence of this genotype in established PCa models and association with cyclin D1b production had yet to be assessed.…”
Section: G͞a870 Polymorphism and Cyclin D1bmentioning
confidence: 99%
See 1 more Smart Citation
“…The A870 polymorphism of cyclin D1 is associated with increased PCa risk (26,27). However, the prevalence of this genotype in established PCa models and association with cyclin D1b production had yet to be assessed.…”
Section: G͞a870 Polymorphism and Cyclin D1bmentioning
confidence: 99%
“…A polymorphism (G͞A870) of the cyclin D1 locus has recently been associated with increased cancer risk for a wide variety of tumors, including PCa (25)(26)(27). Individuals harboring the A870 allele demonstrate an increased propensity to produce an alternatively spliced cyclin D1 mRNA (transcript b).…”
mentioning
confidence: 99%
“…Several studies have identified a correlation between the CCND1 870A allele and an increased cancer risk, including bladder , prostate ,liver and breast cancer (Wang et al, 2002;Wang et al, 2003;Akkiz et al, 2010;Canbay et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have had inconsistent results for an association of the CCND1 A870G polymorphism with bladder cancer (Cortessis et al, 2003;Wang et al, 2003b;Berman et al, 2004;Ito et al, 2004), endometrial cancer (Kang et al, 2005), breast cancer (Grieu et al, 2003;Krippl et al, 2003;Shu et al, 2005), head and neck cancer (Zheng et al, 2001), gastric and oesophageal cancer (Wang et al, 2003c;Zhang et al, 2003a), hepatocellular carcinoma (Zhang et al, 2003b), lung cancer (Qiuling et al, 2003), and prostate cancer (Koike et al, 2003;Wang et al, 2003a). The strongest evidence, to date, has linked the CCND1 A870G polymorphism with an increased risk of colorectal cancer and adenoma in many (Kong et al, 2000(Kong et al, , 2001Bala and Peltomaki, 2001;Porter et al, 2002) though not all studies (McKay et al, 2000).…”
mentioning
confidence: 99%